Fall armyworm management in maize - Singh, S. P.; Patel, Chanchala Rani; Paikra, K. K. (Indian Farming, 2021)
The appearance of new invasive agriculture pest of fall armyworm in Chhattisgarh has made it clear that the pest will cause destruction globally. At this point, the port of entry of the fall armyworm into the State is not yet determined. As this pest is reported to have remarkable dispersal capacity, high reproductive capacity, absence of diapause and wide host range, it is likely to spread to the entire State. Hence, there is urgency for nationwide co-ordinated efforts to contain the pest. The present study may help the growers to through a light on the above said issues.